Konsepsi Strategi Pengembangan Koridor di Tepi Sungai Musi Kota Palembang Sebagai Destinasi Wisata Berdasarkan Persepsi Pengunjung - Sri Lilianti Komariah; Harrini Mutiara Hapsari; Fuji Amalia (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2022)
Kapitan Village and Dewi Kwam In Temple are two tourist destinations in the city of Palembang which are located on the banks of the Musi River. The construction of the corridor along the banks of the Musi River that connects the two tourist areas is still not optimal when viewed from the aspect of satisfaction with the level of service to tourists. Even so, the corridor on the banks of the Musi River has a very high tourism potential because of its very strategic location. This article aims to obtain a conceptualization of a corridor development strategy on the banks of the Musi River based on visitor perceptions as a reference for local government development planning. The research method was carried out using a quantitative method where the statistical data obtained was the result of distributing questionnaires. The data is presented through picture diagrams and analyzed descriptively. Furthermore, the results of the questionnaire are linked to the main principles of waterfront area development. Based on the analysis that has been carried out, the concept of culinary tourism is the type of tourism that is most in demand by respondents and is suitable for application in the Musi Riverside corridor.